超臨界二氧化碳環境下對添加碳化矽套管水泥力學與物化性質之研究 - 謝欣婷; Hsieh, Hsin-Ting (2016)
二氧化碳捕獲與封存是目前公認最有效的減碳技術之一，台灣西部濱海深部鹽水層具有百億噸以上龐大的封存潛能。但封存場址處於高溫、高壓且潮濕環境下，注入的二氧化碳會與水反應形成碳酸，影響隔離套管與井孔岩壁的套管水泥(API-G水泥)並產生碳酸化反應，使得水泥材料的力學性質降低，進而造成二氧化碳洩漏，縮短有效封存的時間。 因此本研究針對上述情形規劃對套管水泥(API-G水泥)及添加不同粒徑(毫米(mm)、微米(μm)、奈米(nm))碳化矽(SiC)之套管水泥進行試驗。試驗規劃分成水泥漿體及水泥塊體，水泥塊體置入模擬井底高溫高壓環境(45°C、25MPa之超臨界二氧化碳溶於去離子水)，觀察經過不同反應時間(未反應、3、7、14、28、56、84天)之物理、化學及微觀性質變化。研究結果發現添加毫米碳化矽(mm-SiC)之套管水泥，可使水泥於反應期間產生緻密層，減緩外部碳酸持續向內部侵蝕並維持其力學強度，有較佳之防止水泥碳化而弱化之能力。 Carbon capture and storage (CCS) is regarded as one of the most effective carbon reduction technologies Deep saline aquifers in the coast of western Taiwan have the potential for storing more than 10 billion tons of CO2 However the storage site is exposed to high temperatures and pressures Consequently Injection of CO2 which reacts with water to form carbonic acid results in the carbonation of the insulating casings as well as casing cement (API Class G) on the borehole This reduces the mechanical properties of the cement material thereby causing CO2 leakage and shortening storage time To address this concern this study conducted experiments on casing cement (API Class G) (America Petroleum Institute abbreviation API) pastes and blocks added with silicon carbide (SiC) of different grain sizes (mm μm nm) Cement blocks were placed in a simulated high-temperature and high-pressure borehole (with supercritical CO2 dissolved in deionized water at 45°C and 25 MPa) to observe the changes in their physicochemical and microscopic properties (0 3 7 14 28 56 84 days) It was observed that during the reaction between CO2 and water a compact layer was formed by mm-SiC carbide casing cement This layer enabled the cement material to attenuate the erosion of carbonic acid arising from supercritical CO2 dissolution in deionized water This maintains the mechanical strength of the cement material and prevents deterioration of cements caused by carbonization